Strigolactones Decrease Leaf Angle in Response to Nutrient Deficiencies in Rice - Shindo, Masato; Yamamoto, Shu; Shimomura, Koichiro; Umehara, Mikihisa (Frontiers in Plant Science, 2020)
Strigolactones (SLs) are a class of plant hormones that are synthesized from β-carotene through sequential reactions catalyzed by DWARF (D) 27, D17, D10, and OsMORE AXILLARY GROWTH (MAX) 1 in rice (Oryza sativa L.). In rice, endogenous SL levels increase in response to deficiency of nitrogen, phosphate, or sulfate (−N, −P, or −S). Rice SL mutants show increased lamina joint (LJ) angle as well as dwarfism, delayed leaf senescence, and enhanced shoot branching. The LJ angle is an important trait that determines plant architecture. To evaluate the effect of endogenous SLs on LJ angle in rice, we measured LJ angle and analyzed the expression of SL-biosynthesis genes under macronutrient deficiencies. In the “Shiokari” background, LJ angle was significantly larger in SL mutants than in the wild-type (WT). In WT and SL-biosynthesis mutants, direct treatment with the SL synthetic analog GR24 decreased the LJ angle. In WT, deficiency of N, P, or S, but not of K, Ca, Mg, or Fe decreased LJ angle. In SL mutants, deficiency of N, P, or S had no such effect. We analyzed the time course of SL-related gene expression in the LJ of WT deficient in N, P, or S, and found that expression of SL-biosynthesis genes increased 2 or 3 days after the onset of deficiency. Expression levels of both the SL-biosynthesis and signaling genes was particularly strongly increased under −P. Rice cultivars “Nipponbare”, “Norin 8”, and “Kasalath” had larger LJ angle than “Shiokari”, interestingly with no significant differences between WT and SL mutants. In “Nipponbare”, endogenous SL levels increased and the LJ angle was decreased under −N and −P. These results indicate that SL levels increased in response to nutrient deficiencies, and that elevated endogenous SLs might negatively regulate leaf angle in rice.